Propriedades magnéticas e magnetocalóricas nos sitemas DyMX (M = Cu e Pt; X = Si e Ge) E R2CuSi3 (R = Eu, Nd e Dy) - SILVA, Mayanny Gomes da (2016)
Here we report the structural, magnetic and magnetocaloric properties of DyMX (M = Cu and Pt; X = Si and Ge) and R2CuSi3 (R = Eu, Nd and Dy) intermetallic compounds. Polycrystalline samples were synthesized by arc melting under argon atmosphere. X-ray diffraction (XRD) analysis by Rietveld method confirm the desired crystallographic phase for all studied samples. Magnetization data show antiferromagnetic ordering around 12.8 K, 4.36 K, 8.7 K and 8.8 K for DyCuSi, DyCuGe, DyPtSi and DyPtGe, respectively. External applied magnetic field induces metamagnetic phase transitions in these compounds. However, the values of magnetic moment in T = 2 K and H = 5T () were lower than the respective values of the R ion effective magnetic moment, indicating that not all magnetic moments are oriented to the external applied field, in H = 5T. Eu2CuSi3 compound presented two ferromagnetic transitions at ܶ = 39.5 K and ܶ = 30 K for H ≤ 0.2 T. On the other hand, Nd2CuSi3 end Dy2CuSi3 magnetization data present characteristic of spin glass behavior in low temperatures (T ≤ 5.6 K for R = Nd e T ≤ 9.5 K for R = Dy) and low magnetic field (H < 0.2 T). When the external magnetic field increase, the magnetization increase faster and show saturation tendency in H = 5 T which indicate ferromagnetic interaction. Our results show a significant magnetocaloric effect (MCE) for all studied samples, which was characterized by a broad peak in the entropy variation change curves ሺȂ οܵ௠ሻ associated with the magnetic transition. The maximum MCE was obtained for DyCuSi compound ( = 23.7 J/kg.K and ܴܥ = ܲ421.5 J/kg), which indicate that this compound belongs to the class of magnetic materials with giant magnetocaloric effect. Large MCE was obtained for DyCuGe, Nd2CuSi3 e Dy2CuSi3 ( values ranging from 11.4 to 14.8 J/kg K). While conventional MCE was observed for DyPtGe, DyPtGe and Eu2CuSi3 compound values ranging from 8.1 to 11.2 J/kg.K). The obtained results, indicate that the DyMX and R2CuSi3 studied compound present interesting characteristics for application as refrigerant material in cryogenic temperatures.